Strategi Klasterisasi UMKM Berbasis Kearifan Lokal pada Kabupaten dan Kota di Provinsi Jambi - Lubis, Tona Aurora; Machpudin, Asep; Putra, Wirmie Eka; Ningsih, Maryati (Ekonomis: Journal of Economics and Business, 2024)
This study aimed to assess how local wisdom integration and clustering strategies impact the performance of Micro, Small, and Medium Enterprises (MSMEs) in Jambi Province, using a mixed-method approach. It was found that both local wisdom and clustering significantly enhance MSME performance by adding value, differentiating products, and improving access to resources, innovation, and operational efficiency. The research underscores the critical role these strategies play in MSME development. Consequently, it suggests that MSME managers, investors, and policymakers should support initiatives promoting the integration of local wisdom and the development of clusters to boost MSME competitiveness and growth in Jambi Province. This approach demonstrates a viable pathway for MSMEs to enhance their performance and sustainability.